Drug use: perception of parents and adolescents - Pulido-Trujillo, Saraí; De San Jorge-Cárdenas, Xóchitl; Morales-Contreras, Nora Inés; Peregrina Martínez, María del Pilar (Horizonte Sanitario, 2024)
Objective: to know and compare the perception of parents and adolescents on the role of the family in the prevention of drug use. Materials and methods: Qualitative research, conducted in May 2022, in which group interviews were applied through the instrument called focus group, two groups were integrated, one with adolescents (five boys and six girls) and another with parents (one boy and eight girls), with no parental relationship between the groups, randomly recruited, belonging to the same high school in the city of Xalapa, Veracruz. After reading and signing the informed consent, answers were given to the nine questions of the questionnaire. Results: for the analysis of the information, discourse analysis was used, which technique studies what was said according to the context, which allowed us to compare what was expressed in both groups. Parents perceive that they provide trust, while adolescents perceive that they do not; parents perceive that their children have the necessary knowledge about drug use, while adolescents are concerned to know about the risks, parents perceive that their children have no lacks, no needs, while adolescents manifest insufficient love and attention from their parents. Conclusions: Parents and children have a different view on drug use and on the role of the family in prevention. The need to generate spaces for reflection that allow for greater communication between parents and children was identified.